The Legacy of Local Wisdom Education Models for The Next Generation of Toraja, Indonesia - Tarrapa, Setrianto; Junaedi, I Wayan Ruspendi; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2021)
This paper presents several reflections, structured around the theme of local wisdom, on classical and experimental patristic education visions. A depiction of Toraja local wisdom on something more than human attainment or divine attributes. Finally, this paper can be a legacy of local wisdom education models that are passed down to the next generation. This study describes that the value of education in Tongkonan has existed since the primitive times of the Toraja people, played in every aspect of life. The cultural learning experiment in Tongkonan begins with working solidarity and ends with the distribution of food in the form of pork and buffalo meat. Such educational dynamics occur in joyful mourning and thanksgiving ceremonies for Toraja traditional houses and the face of tough work. Philosophy of learning The basic thing that can be found in the Toraja culture is hard work and sincerity, solidarity with others in fellowship. The value of education in Tongkonan has existed since the primitive days of the Toraja people, by developing an educational model or experimental learning in Tongkonan with a cybernetics system, namely the first party to educate children in the family than the second party in the model. patron-client for generations.